Determinants of Profitability Among Agricultural Equipment Fabricators in Oyo State, Nigeria - Benjamin Oyelami; Adegbenga Adekoya; Iredele Ogunbayo; Oreoluwa Akano; Enya Effa; Adetola Oyegbile; Olubusayo Olorunkoya; Genesis Osadebamwen; Peace Aburime (Journal of Agricultural Extension, 2024)
The study examined enterprise profitability among agricultural equipment fabricators. It was conducted in Oyo State, Nigeria using a multistage sampling procedure to select the 48 respondents from whom data were collected using a structured questionnaire. Percentage was used to analyse the socioeconomic and enterprise characteristics of the respondents, while gross margin analysis was used to determine the profitability of the enterprise. A linear regression model was used to ascertain the drivers of enterprise profitability among respondents. Findings revealed that over half (54.4%) of the fabricators produced processing equipment, while fewer (28.2%) produced farm tools. Most of the fabricators operated with a mean workshop space of 1.3 m2. The gross margin analysis showed a total revenue of N95,302,900 exceeding the total cost of production (N20,374,205), indicating (N74,928,695) profitability of their enterprise with a N3.68 return on investment per Naira. Fabrication being a secondary occupation (?=0.340), and business registration with the Corporate Affairs Commission (?=0.473) significantly influenced profitability among the respondents. This study recommends regulating the fabrication sector through policies, ensuring that fabricators register their outfits, provision of credit, and training by the government to significantly enhance the standardization of outputs and increase the units of production, hence, improving the enterprise's profitability.